(untitled) (CIPEEX, 2024)
THE PLANNED PLATFORM WILL BE CALLED MEAT SHOP, AND THE PROPOSAL IS THAT IT CAN INNOVATE THE BUTCHERY BUSINESS BY PROVIDING A NEW WAY OF BUYING MEAT AND MEAT PRODUCTS. IN ORDER TO IMPROVE THE WAY TASKS ARE CARRIED OUT ON A DAILY BASIS, APPS ARE BECOMING MORE AND MORE COMPLETE IN ORDER TO MEET ALL THE NEEDS OF THEIR USERS QUICKLY AND INTUITIVELY. HOWEVER, THE BUTCHER’S MARKET IS UNDERDEVELOPED IN THIS RESPECT AND ENDS UP BEING LIMITED TO FACE-TO-FACE AND/OR TELEPHONE ORDERS, MAKING THE SALE OF THESE PRODUCTS MORE BUREAUCRATIC. FOREMOST, A SURVEY AND STATISTICAL ANALYSIS WERE CARRIED OUT IN ORDER TO UNDERSTAND THE NEEDS OF THE MARKET, AND AROUND 95% OF THE PEOPLE INTERVIEWED SAID THAT THEY GO TO THE BUTCHER’S IN PERSON TO BUY MEAT, AND 42% SAID THAT GOING TO THE BUTCHER’S TAKES UP A LOT OF THEIR TIME ON A DAILY BASIS. THAT’S WHY THIS SOFTWARE AIMS TO PROVIDE CUSTOMERS IN THIS SECTOR WITH AN EASY AND PERSONALIZED SHOPPING EXPERIENCE. IN IT, PROBLEMS SUCH AS NOISES IN COMMUNICATION, WHICH OFTEN HINDER PURCHASES IN THE TRADITIONAL METHOD, WILL NOT OCCUR. IN ADDITION, IT WILL SPEED UP THE ORDERING PROCESS; CUSTOMERS WILL BE ABLE TO VIEW THE PRODUCTS AVAILABLE IN STOCK, REPEAT ORDERS ALREADY PLACED USING A PURCHASE HISTORY, SCHEDULE FUTURE ORDERS, RECEIVE TIPS ON FAVORITE CUTS, COMPARE PRICES BETWEEN ESTABLISHMENTS, AND TRACK THE PROGRESS OF THEIR DELIVERIES. IN ADDITION, THE PROJECT’S REQUIREMENTS WERE GATHERED, AND AN MVP (MINIMUM VIABLE PRODUCT) WAS CREATED TO MEET THE USERS’ MAIN NEEDS, IN ORDER TO LATER IMPLEMENT THE FUNCTIONALITIES THAT WERE INITIALLY CONSIDERED UNNECESSARY BUT, ACCORDING TO USER FEEDBACK, COULD BE CONSIDERED USEFUL AND ATTRACTIVE AT A CERTAIN POINT. THE PLATFORM WILL BE DIVIDED INTO A FEW STAGES: CHOOSING THE ESTABLISHMENT, CUT, QUANTITY, DELIVERY ADDRESS, PAYMENT METHOD AND EVALUATION. IN THIS WAY, IT CAN BE CONCLUDED THAT THE IDEA WILL BRING SEVERAL BENEFITS TO THE SECTOR, SUCH AS: AN INCREASE IN SALES, SINCE EVEN WITH LITTLE TIME FOR DAILY TASKS, PEOPLE WILL BE ABLE TO MAKE THEIR PURCHASES WITH A FEW CLICKS AND QUICKLY; A REDUCTION IN THE RATE OF WRONG ORDERS, SINCE COMMUNICATION NOISE IS ALMOST NON-EXISTENT IN APP-BASED PURCHASES; SPEED AND AGILITY IN EVERYDAY LIFE, SINCE YOU DON’T HAVE TO GO TO THE LOCATION TO ORDER, AVOIDING TRAFFIC AND OTHER RELATED PROBLEMS; GREATER CUSTOMER REACH, SINCE MANY PEOPLE DON’T LIKE TO GO VERY FAR TO BUY THEIR PRODUCTS, WHILE THE APPLICATION DOES NOT HAVE THIS PROBLEM. THE SOFTWARE IS STILL UNDER DEVELOPMENT BUT HAS MADE GOOD PROGRESS AND IS CURRENTLY AT THE DESIGN STAGE: CREATING THE VISUAL IDENTITY AND LAYOUT OF ELEMENTS, FUNCTIONALITY TESTS AND RESEARCH INTO THE BEST WAY TO ORGANIZE THE FLOW OF INFORMATION. THERE IS STILL A LOT TO DO, BUT IT HAS MADE SOLID PROGRESS SO FAR, WHICH HAS BEEN WELL ACCEPTED BY THE USERS TO WHOM IT HAS BEEN DEMONSTRATED.